Developing Instruments Assessment of Students' Critical Thinking and Communication Skills in Biology Learning Using Hybrid Learning Models in 3T Areas - Wakano, Rafsan; Isnaeni, Wiwi; Ahmadi, Farid (Universitas Negeri Semarang, 2022)
The availability of instruments for measuring critical thinking and communication skills for class X SMA Negeri 15 Seram Barat is still limited, so it needs to be developed. This study developed an essay model assessment instrument consisting of 10 questions. Using the Mardapi development model consists of 10 steps. The results of the validity and reliability analysis using the Ikens'V and TwoWayAnnova formulas, the average score obtained is 0.73 for critical thinking skills and 0.64 for communication skills where the score exceeds the standard coefficient of 0.3, then it can be declared valid . While the measurement of reliability with the Eibel formula obtained a score of 0.78 critical thinking skills and 0.82 communication skills, it entered the very high category, so it can be concluded that the critical thinking and communication skills assessment instrument can be said to be valid and reliable. Field analysis data seen from the KMO score of 0.835 indicates that the KMO value is >0.5 so that the instrument items can be analyzed further. The results on the RotatedComponentMatrixaform 2 factors which are named 1) the ability to analyze and solve problems 2) the ability to convey ideas concretely. Furthermore, the results of reliability testing with the Cronbachs alpha get the results of 0.654 or >0.6. From the results of these tests, it can be concluded that the instrument for assessing critical thinking and communication skills has good validity and reliability, so this instrument is expected to be used later by teachers as a reference or guide for teachers to measure critical thinking and communication skills.